2017
DOI: 10.1177/2158244017697155
|View full text |Cite
|
Sign up to set email alerts
|

Student Outcomes From Participating in an International STEM Service-Learning Course

Abstract: The purpose of this study was to measure student affective, behavior, and content (ABC) and global awareness outcomes after participating in a science, technology, engineering, and mathematics (STEM)–based international service-learning (ISL) course and impacts on long-term retention in STEM fields. We compared experiences from 12 participants (undergraduate and graduate students) enrolled in a STEM-based ISL course with experiences from four students enrolled in the same course without the service-learning co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
(26 reference statements)
0
16
0
8
Order By: Relevance
“…The findings of the study support previous long-term research in that many students consider SL a significant experience in college (Fullerton et al 2015;Jorge 2011). They also affirm the identification of SL as a high impact educational practice (Kuh 2008) that promote longterm gains in affective, behavioral, content, and civic awareness outcomes, such as intercultural sensitivity, openness to diversity, and social responsibility (Daniel and Mishra 2017;Fullerton et al 2015;Kilgo et al 2015) as well as for some students, service-oriented employment choices (Warchal and Ruiz 2004).…”
Section: Discussion and Implications For Teachingmentioning
confidence: 75%
See 1 more Smart Citation
“…The findings of the study support previous long-term research in that many students consider SL a significant experience in college (Fullerton et al 2015;Jorge 2011). They also affirm the identification of SL as a high impact educational practice (Kuh 2008) that promote longterm gains in affective, behavioral, content, and civic awareness outcomes, such as intercultural sensitivity, openness to diversity, and social responsibility (Daniel and Mishra 2017;Fullerton et al 2015;Kilgo et al 2015) as well as for some students, service-oriented employment choices (Warchal and Ruiz 2004).…”
Section: Discussion and Implications For Teachingmentioning
confidence: 75%
“…Likewise, Fullerton et al (2015) indicated that participation in a SL General Education Capstone course at Portland State University had a lasting impact on graduates' perspectives, including communication skills, maturity, deeper understanding of, and appreciation for, diversity, and a desire to serve. Additionally, examining the impact of a STEM-based SL course, Daniel and Mishra (2017) observed that SL students demonstrated gains in affective, behavioral, content, and civic awareness outcomes.…”
Section: Long-term Impact Of Service-learning Across Disciplinesmentioning
confidence: 99%
“…In a community college sample, Prentice and Robinson (2010) found that SL participation predicted superior student learning outcomes including higher scores on measures of teamwork, civic responsibility, academic development, and educational success across courses and disciplines. Similarly, when comparing students who completed a SL course to students who completed the same course without the SL component, Daniel and Mishra (2017) found that service learners experienced positive improvements in affective outcomes, civic awareness, and specific content knowledge. Additionally, Litchke and colleagues (2020) reported positive mental health changes among therapeutic recreation college students who engaged in SL with youth involved in a social inclusion program.…”
Section: Benefits Of Slmentioning
confidence: 99%
“…Langhout and Gordon (2019) suggested SL may be a particularly engaging approach for underrepresented and misrepresented students since it lessens the fissure between the university cultural community and the home cultural community. Similarly, Daniel and Mishra (2017) suggested that SL may relate to long-term retention in Science Technology Engineering, and Mathematics (STEM). Two years after participating in a SL course, students reported that understanding how to integrate science with community involvement influenced their career path.…”
Section: Benefits Of Slmentioning
confidence: 99%
“…That means that SWU is willing to cover more than half of the costs because they think GS-L has a big possibility to achieve the educational purpose of SWU. GS-L or international experiential programs allow participants to open their minds to different cultures and to develop intercultural competence and global civic awareness [2][3][4][5]. According to the findings from those case studies and the main objectives of GS-L, the research questions are as followings:…”
Section: Introductionmentioning
confidence: 99%